2021
DOI: 10.3390/foods10020241
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Pulsed Electric Fields on the Technological Properties of Chicken Meat

Abstract: Pulsed electric field (PEF) is a non-thermal technology which is increasingly drawing the interest of the meat industry. This study aimed at evaluating the effect of PEF on the main technological properties of chicken meat, by investigating the role of the most relevant process parameters such as the number of pulses (150 vs. 300 and 450 vs. 600) and the electric field strength (0.60 vs. 1.20 kV/cm). Results indicated that PEF does not exert any effect on meat pH and just slightly affects lightness and yellown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The observed minimal effect of ultrasound pretreatment on chicken breast meat pH suggests that the chosen parameters did not induce substantial alterations in cellular structures or promote the release of intracellular components that could significantly influence pH [33] . Similarly, previous studies found a non-significant impact of different PEF treatments (0.60–1.20 kV/cm) on the pH values of chicken [27] and beef [35] , [36] . Conversely, PEF treatment, particularly at higher intensities, has a clear influence on muscle tissue pH [37] .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The observed minimal effect of ultrasound pretreatment on chicken breast meat pH suggests that the chosen parameters did not induce substantial alterations in cellular structures or promote the release of intracellular components that could significantly influence pH [33] . Similarly, previous studies found a non-significant impact of different PEF treatments (0.60–1.20 kV/cm) on the pH values of chicken [27] and beef [35] , [36] . Conversely, PEF treatment, particularly at higher intensities, has a clear influence on muscle tissue pH [37] .…”
Section: Resultssupporting
confidence: 70%
“…The hue angle (h 0 ), saturation ( C* ), and total color difference (ΔE) were determined using the following equations: Where L* values measure darkness to lightness (larger values indicate a lighter color), whereas a* value measures redness (positive values indicate a redder color, and negative values indicate a greener color). However, b* values measure yellowness (positive values indicate yellowness, and negative values indicate blueness) [27] .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, breakage around the Z-disk could allow water to flow from the outside myofibrils space to inside, thereby increasing WHC (Zeng et al, 2017). However, very few studies have reported the effect of PEF treatment on chicken meat quality (Gudmundsson & Hafsteinsson, 2001;Khan et al, 2017;Baldi et al, 2021). To the best of our knowledge, this is the first study to report the effect of the synergistic treatment of PEF and CaCl 2 on water retention in chicken breast meats.…”
Section: Introductionmentioning
confidence: 92%
“…PEF to reduce the undesired liquid inside the package. Faridnia et al, 2015;Baldi et al, 2021;Karki et al, 2022 Peptides isolated from pine and pecan nuts Preservation -1800 Hz and 15 kV/cm. PEF have been reported to increase the total oil extraction yield…”
Section: Materials Pef Parameters Effect Of Pef Referencesmentioning
confidence: 99%